ATLANTIS IN SPAIN II - Papamarinopoulos, S.P. (Bulletin of the Geological Society of Greece, 2010)
Plato, who lived in the 4th century B.C., wrote the dialogue Timaeos and Critias when he was 52 years old. In this he describes a catastrophe in Athens from an earthquake in the presence of excessive rain. He also describes several details, not visible in his century, in the Acropolis of Athens. These details are a spring and architectural details of buildings in which the warriors used to live. In Critias he mentions that the destruction of the spring was caused by an earthquake. The time of the catastrophe of Atlantis was not defined by him but it is implied that it occurred after the assault of the Atlantes in the Mediterranean. Archaeological excavations confirmed the existence of the spring which was about 25 m deep with respect to the present day walking level. Archaeologically dated ceramics, found at its bottom, denote the last function of the spring was in very early 12th century B.C. Plato describes the warriors’ settlements which were found outside of the fortification wall in the North East of the Acropolis. The philosopher, who was not a historian, describes a general catastrophe in Greece from which the Greek language survived till his century. Archaeological studies have offered a variety of tablets of Linear B writings which turn out to be the non-alphabetic type of writing of the Greeks up to the 12th century B.C. before the dark ages commence. Modern geoarchaeological and palaeoseismological studies prove that seismic storms occurred in the East Mediterranean between 1225 and 1175 B.C. The result of a fifty-year period of earthquakes was the catastrophe of many late Bronze Age palaces or settlements. For some analysts both Athens and Atlantis presented in Timaeos and Critias are imaginary entities. They maintained that the imaginary conflict between Athens and Atlantis served Plato to produce the first world’s “science fiction” and gave the Athenians an anti-imperialistic lesson through his fabricated myth. However, a part of this “science fiction”, Athens of Critias, is proved a reality of the 12th century B.C., described only by Plato and not by historians, such as Herodotus, Thucydides and others. Analysts of the past have mixed Plato’s fabricated Athens presented in his dialogue Republic with the non-fabricated Athens of his dialogue Critias. This serious error has deflected researchers from their target to interpret Plato’s text efficiently.